2013
DOI: 10.1007/s10529-013-1306-3
|View full text |Cite
|
Sign up to set email alerts
|

Fungal treatment followed by FeCl3 treatment to enhance enzymatic hydrolysis of poplar wood for high sugar yields

Abstract: Fungal treatment followed by FeCl3 treatment was used to improve saccharification of wood from Populus tomentosa. Combined treatments accumulated lignin and slightly degraded cellulose, whereas almost all hemicelluloses were removed. The white rot fungus, Trametes orientalis, and the brown rot fungus, Fomitopsis palustris, both accompanied by FeCl3 post-treatment resulted in 98.8 and 99.7 % of hemicelluloses loss at 180 °C, respectively, which were over twice than that of hot water pretreatment at the same lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Gui et al (2013) combined a fungal treatment using P. chrysosporium with 2.5% sulphuric acid treatment and obtained glucose yields 1.08-1.71 times higher than in acid-treated Glycyrrhiza uralensis under the same conditions. Wang et al (2013b) reported that fungal pretreatment of poplar wood with Trametes orientalis (white-rot fungus) or Fomitopsis palustris (brown-rot fungus) followed by FeCl 3 treatment increased sugar yields 1.4 and 1.6 times more than FeCl 3 treatment alone. Only Yang et al (2013) observed a similar enhancement of bioconversion to that found in this study through synergistic treatment of poplar with a four-week white-rot fungus T. velutina D10149 pretreatment and alkaline fractionation (1% NaOH, 75°C, 3 h), obtaining a glucose yield of 38.8%.…”
Section: Autohydrolysis and Fungal Pretreatment Combinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gui et al (2013) combined a fungal treatment using P. chrysosporium with 2.5% sulphuric acid treatment and obtained glucose yields 1.08-1.71 times higher than in acid-treated Glycyrrhiza uralensis under the same conditions. Wang et al (2013b) reported that fungal pretreatment of poplar wood with Trametes orientalis (white-rot fungus) or Fomitopsis palustris (brown-rot fungus) followed by FeCl 3 treatment increased sugar yields 1.4 and 1.6 times more than FeCl 3 treatment alone. Only Yang et al (2013) observed a similar enhancement of bioconversion to that found in this study through synergistic treatment of poplar with a four-week white-rot fungus T. velutina D10149 pretreatment and alkaline fractionation (1% NaOH, 75°C, 3 h), obtaining a glucose yield of 38.8%.…”
Section: Autohydrolysis and Fungal Pretreatment Combinationsmentioning
confidence: 99%
“…The combination of fungal and physical or chemical pretreatments can potentially overcome recalcitrance, improving the yields of end products. Pretreatments with mild acid (Gui et al, 2013), alkali (Salvachúa et al, 2011;Yang et al, 2013;Zhong et al, 2011), organosolv (Muñoz et al, 2007), hydrogen peroxide (Yu et al, 2009), FeCl 3 (Wang et al, 2013b) and thermal treatments (López-Abelairas et al, 2013) have been combined with fungal pretreatments to increase saccharification yields. These combinations would also diminish the severity of chemical and/or physical pretreatments, minimising some of the disadvantages, such as the formation of inhibitory compounds (López-Abelairas et al, 2013;Wang et al, 2013a), and/or reducing fungal treatment times (Yu et al, 2009;Zhong et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…MA has been used as a simple, effective, and environmentally friendly physical pretreatment to destroy the recalcitrant structure of lignocellulose and stable crystal structure of cellulose, and change the chemical structures of lignin [1720]. Metal salts can be used for the pretreatment of cellulosic materials by disrupting the hydrogen bonds, reducing the crystallinity of cellulose, and aiding in the cleavage of glycosidic linkages, which result in the enhancement of enzymatic digestibility [21]. Metals salts are especially fascinating as pretreatment agents because of their lower corrosivity than inorganic acids [22].…”
Section: Introductionmentioning
confidence: 99%
“…The tremendous hemicelluloses degradation was attributed to the ability of Fe 3+ ion in FeCl3 to act as good electron acceptor capability and synchronize with the oxygen donor atoms of carbohydrates to hydrolyze hemicelluloses (Yu et al, 2011). This masked the synergy of the combined biological-oxidative pretreatment in hemicelluloses degradation (Wang et al, 2013b). Zhang et al…”
Section: Biological -Oxidative Pretreatmentmentioning
confidence: 99%